Teachers' Beliefs about the Possibilities and Limitations of Digital Games in Classrooms. (December 2014) - Beavis, Catherine; Rowan, Leonie; Dezuanni, Michael; McGillivray, Christie; O'Mara, Joanne; Prestridge, Sarah; Stieler-Hunt, Colleen; Thompson, Roberta; Zagami, Jason
Teachers' beliefs about what it is (or is not) possible to achieve with digital games in educational contexts will inevitably influence the decisions that they make about how, when, and for what specific purposes they will bring these games into their classrooms. They play a crucial role in both shaping and responding to the complex contextual factors which influence how games are understood and experienced in educational settings. Throughout this article the authors draw upon data collected for a large-scale, mixed-methods research project focusing on literacy, learning and teaching with digital games in Australian classrooms, to focus explicitly on the attitudes, understandings and expectations held about digital games by diverse teachers at the beginning of the project. They seek to identify the beliefs about games that motivated teachers' participation in a digital games research project while focusing, as well, on concerns that teachers express about risks or limitations of such a project. The authors' aim is to develop a detailed picture of the mindsets that teachers bring to games-based learning environments, and the relevance of these mindsets to broader debates about the relationship between games, learning and school.